2021
DOI: 10.3389/fphar.2021.642398
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor Agonist Inhibits Atrial Electrical Remodeling in a Tachypaced Ex Vivo Rat Model

Abstract: Introduction: Atrial fibrillation (AF) leads to rate-dependent atrial changes collectively defined as atrial remodelling (AR). Shortening of the atrial effective refractory period (AERP) and decreased conduction velocity are among the hallmarks of AR. Pharmacological strategies to inhibit AR, thereby reducing the self-perpetual nature of AF, are of great clinical value. Cannabinoid receptor (CBR) ligands may exert cardioprotective effects; CB13, a dual CBR agonist with limited brain penetration, protects cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 82 publications
(114 reference statements)
1
12
0
Order By: Relevance
“…Our findings demonstrate that the CBR ligand, CB13, attenuates atrial myocyte enlargement and mitochondrial dysfunction in NRAM through AMPK signaling, building upon previous evidence for beneficial effects of CBR ligands in stressed cardiomyocytes (Lu et al, 2014;Lu et al, 2020;Lee et al, 2021). In addition, our data may suggest that AMPK-dependent changes in Cx43 expression also contribute to the possible beneficial effect of CBR ligands.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our findings demonstrate that the CBR ligand, CB13, attenuates atrial myocyte enlargement and mitochondrial dysfunction in NRAM through AMPK signaling, building upon previous evidence for beneficial effects of CBR ligands in stressed cardiomyocytes (Lu et al, 2014;Lu et al, 2020;Lee et al, 2021). In addition, our data may suggest that AMPK-dependent changes in Cx43 expression also contribute to the possible beneficial effect of CBR ligands.…”
Section: Discussionsupporting
confidence: 81%
“…For example, blocking the inner membrane ion channel, IMAC, was protective against arrhythmias by preventing ΔΨ m reduction, improving left ventricular developed pressure, and preventing action potential shortening (Billman et al, 1998;Aon et al, 2003;Brown et al, 2008). As noted above, we recently reported that CB13 treatment prevents atrial refractoriness shortening in an ex vivo rat model exposed to atrial tachypacing, suggesting prevention of action potential shortening by CB13 (Lee et al, 2021). It is plausible that CB13 counteracted the tachypacing-related remodeling by modulating ΔΨ m via IMAC.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…CB 1 -Rs and CB 2 -Rs were also identified in hearts of the guinea pig [ 72 ], rat [ 73 , 74 , 75 ], and mouse [ 76 , 77 ]. In detail, these receptors occur in the left ventricle [ 78 , 79 ] and left atrium of the rat [ 80 ], and in the left ventricle of the dog [ 81 ] and the mouse [ 67 , 82 , 83 ].…”
Section: Endocannabinoid System In Humans and In Experimental Animals...mentioning
confidence: 99%
“…Moreover, prolongation of the AP in response to THC was found in sheep Purkinje fibers (receptor not determined; [ 197 ]). The synthetic agonist CB13 inhibited the tachypacing-induced shortening of the rat atrial effective refractory period protecting against atrial fibrillation (receptor not identified; [ 80 ]).…”
Section: Other Factorsmentioning
confidence: 99%